2009
DOI: 10.1007/s10665-009-9347-2
|View full text |Cite
|
Sign up to set email alerts
|

What makes the Peregrine soliton so special as a prototype of freak waves?

Abstract: The formation of breathers as prototypes of freak waves is studied within the framework of the classic 'focussing' nonlinear Schrödinger (NLS) equation. The analysis is confined to evolution of localised initial perturbations upon an otherwise uniform wave train. For a breather to emerge out of an initial hump, a certain integral over the hump, which we refer to as the "area", should exceed a certain critical value. It is shown that the breathers produced by the critical and slightly supercritical initial pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
210
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(215 citation statements)
references
References 33 publications
3
210
0
2
Order By: Relevance
“…[27], [5], [10] and references therein). Some of them relate the rogue wave appearance to the development of modulational instability of the plane wave due to small perturbations (see, e.g., [30], [1], [17]) or large-scale initial modulations [34], [18]. Other proposed mechanisms involve interactions of individual solitons [14], [32] or interaction of solitons with the plane wave [41].…”
Section: Introductionmentioning
confidence: 99%
“…[27], [5], [10] and references therein). Some of them relate the rogue wave appearance to the development of modulational instability of the plane wave due to small perturbations (see, e.g., [30], [1], [17]) or large-scale initial modulations [34], [18]. Other proposed mechanisms involve interactions of individual solitons [14], [32] or interaction of solitons with the plane wave [41].…”
Section: Introductionmentioning
confidence: 99%
“…The validity of the NLS has been experimentally confirmed even in the modelling of extreme localisations, beyond its well-known asymptotic limitations [4][5][6][7][8], and due to its interdisciplinary character analogies being able to be built into other nonlinear dispersive media, such as in optics [9], a research field in which several NLS applications have found strong interest [9][10][11][12][13][14]. Furthermore, the NLS admits basic models for the description of oceanic extreme events known as breathers [15][16][17]. Indeed, the family of Akhmediev breathers (ABs) [18] and Peregrine breathers [18,19] are strongly connected to the modulation instability (MI), also known as Benjamin-Feir instability [20], of Stokes waves [21].…”
Section: Introductionmentioning
confidence: 99%
“…Wave profiles and dynamics are discussed in Section IV, where special attention is paid to the possibility of reaching higher than normal RW amplification ratio. A gauge transformation connecting the present system 6 and other models studied in the literature is presented in Section V, together with a discussion on applications to optics and plasma physics. Conclusions are drawn in Section VI.…”
Section: Introductionmentioning
confidence: 99%